The hamstring stretch angle: a screening and monitoring tool for canine fibrotic myopathy - Birdwhistell, Kate Elizabeth; Miscioscia, Erin; Montalbano, Christina; Repac, Jennifer (Frontiers in Veterinary Science, 2025)
IntroductionFibrotic myopathy of the gracilis, semimembranosus, and semitendinosus muscles is an uncommon disease in dogs and has been primarily described in working line German Shepherds. Fibrotic myopathy can dramatically shorten the working life of military working dogs and is thus an economically important disease given the substantial cost of training. The primary objective of this study was to establish reference ranges for hamstring stretch angles from unaffected German Shepherds and unaffected retrievers (Goldens and Labradors). The secondary objective was to compare these unaffected dog hamstring stretch angles to those from German Shepherds affected with fibrotic myopathy.MethodsThirty dogs (20 angles per group) were used to compare a total of 60 hamstring stretch angles. The hamstring stretch angle was defined as the angle of stifle extension while the hip was held in hyperflexion. Twenty unaffected German Shepherds and retrievers were prospectively recruited for inclusion in this study to establish normal reference ranges and compared to retrospective measurements of German Shepherds affected with fibrotic myopathy. Receiver operator characteristic curves were generated to establish a cut off value for fibrotic myopathy screening.ResultsThe mean hamstring stretch angle was 147° for the unaffected shepherds and retrievers and 109° for the affected German Shepherds. There was no significant difference in the hamstring stretch angles between unaffected German Shepherds and the retrievers. There was a mean 37° difference between the affected German Shepherd group when compared to the unaffected German Shepherds and the retrievers (p < 0.0001). A hamstring stretch angle of 136° was determined to be the cutoff value for further fibrotic myopathy screening with a sensitivity of 100% and specificity of 100%.ConclusionThe hamstring stretch angle may serve as a quick, inexpensive, and noninvasive method to screen for fibrotic myopathy of the gracilis, semimembranosus, or semitendinosus muscles and future research is indicated to evaluate its use as a monitoring tool for disease progression.